Writing the smart city: "relational space" and the concept of "belonging" - Jordan, Spencer (National Association of Writers in Education, 2015)
This paper explores McQuire’s concept of "relational space", a term he uses to describe the transformed horizon of social relationships within the smart city. Although there is no exact definition, the smart city is predicated on both the rise of digital technology and ubiquitous wireless connectivity. The city, of course, has always been intimately connected with technology. Yet it is clear that this most recent innovation constitutes a significant reconfiguration of the urban experience. Possibilities abound in terms of how citizens might interact with services, the environment and each other. Yet, this paper argues that these transformations are intimately linked to wider changes in thought and experience. As post-industrial cities become more complex, and their communities more dispersed, questions such as "where is home?" and "where and how do I belong?" become increasingly pertinent for a deeper, more sustained understanding of "relational space" and its impact on how we might experience our lives. This paper, drawing on the outcomes of a small project, argues that creative writing can play a fundamental role within the development of the smart city, empowering citizens to redefine "relational space" in terms of our deeper need for "home".